Expenditure Pattern of Small and Marginal Farmers (A Case Study in Mukhed Taluka of Nanded District) - Awade, Nagorao H (Journal of Commerce and Trade, 2009)
India is a agricultural country. Majority of the farmers are classified as small & marginal farmers having a land holding of less than 5 acres. These farmers are generally living below poverty line and their problems have a special importance in rural economic growth and development. Income of a farmer determined by the size of holding i.e. the land owned and possessed by the farmer. Higher the size of holding higher is the income potential. Higher the income potential higher is the socio-economic status. Present study is related with the group of small and marginal farmers living in economically backward region of Marathwada in Maharashtra. This study of expenditure pattern highlights the overall pattern of expenditure of small & marginal farmers.